Higher Chocolate Candy Intake Is Associated with Longer Telomere Length Among Adolescents (P01-018-19). (13th June 2019) - Chen, Li; Zhu, Haidong; Gutin, Bernard; Sesso, Howard; Dong, Yanbin
Abstract: Objectives: Chocolate intake has been shown to improve lipid profiles, which is associated with longer leukocyte telomere length (LTL). But the relationship between chocolate candy intake and cellular aging has not been investigated. We aimed to examine the association between chocolate intake and LTL in adolescents with comprehensive assessments of dietary, lifestyle, and clinical risk factors. Methods: The dietary chocolate candy intake information were available in 660 adolescents aged from 14 to 18 years (51% girls and 48% blacks). The chocolate candy intake was estimated by seven independent 24 h dietary recalls and divided into three groups, which were none, less than 2 servings/week, and 2 servings/week or more. Multiple linear regression was performed to investigate the association between chocolate intake and LTL. Results: Among the adolescents, 383 (58%) didn't take any chocolate during dietary recall periods, 165 (25%) consumed chocolate less than 2 servings/week (1.1 ± 0.5 servings/week), and 122 (17%) consumed chocolate of 2 servings/week or more (4.7 ± 4.0 servings/week). Body mass index (BMI) or % body fat was inversely related to chocolate intake in a dose-response fashion ( p s < 0.01). Chocolate consumption was also positively associated with ApoA1 ( P = 0.024) and ApoA1/HDL ( P = 0.036). In addition, ApoA1 and ApoA1/HDL were positively associated with LTL ( p s = 0.044 and 0.003, respectively). Compared to non-consumers, adolescents who consumed chocolate of ≥2 servings/week had 0.26 standard deviation longer LTL ( P = 0.016) when adjusted for age, sex and race. The association remained significant after further adjustment of BMI, energy intake, the Alternate Healthy Eating Index (AHEI), non-chocolate candy intake, physical activity, family SES and sexual development. Conclusions: Adolescents who consume 2 servings/week or more of chocolate have longer LTL compared with non-consumers, and ApoA1-HDL pathway might be underlying the chocolate-LTL relationship. Further intervention studies are warranted to verify the beneficial effect of chocolate candy intake on the cellular aging process. Funding Sources: Study was in part supported by the National Institute of Health, grant number HL064157.